Edukasi Dan Sosialisasi Cuci Tangan Pakai Sabun Di KB – TK Aisyiyah Kureksari Pasca Pandemi Covid-19 - Anindita Riesti Retno Arimurti; Ellies Tunjung Sari Maulidiyanti; Fitrotin Azizah; Nur Vita Purwaningsih; Dita Artanti; Yeti Eka Sispita Sari (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
The COVID-19 pandemic has changed many aspects of our daily lives, including in the school environment. School is an environment where children learn and interact, making them vulnerable to spreading infectious diseases. Washing hands with soap is a simple tion effective in preventing the spread of viruses and maintaining health in schools. Washing hands with soap is practical in killing viruses and bacteria that stick to hands. Soap has properties that can destroy the fat layer of the virus, so the virus cannot survive. By washing hands with soap regularly, children can reduce the risk of contracting COVID-19 and other infectious diseases. This community court activity consists of three stages: preparation, implementation and evaluation. This community service activity was conducted at KB – TK Aisyiyah 1 Kureksari, Sidoarjo. The method used is in the form of posters and extension demonstrations with movement and music methods. After participating in this activity, students can apply hand washing with soap after activities outside the home or before eating.